Channel Models, Favorable Propagation and MultiStage Linear Detection in Cell-Free Massive MIMO - Gholami, Roya; Cottatellucci, Laura; Slock, Dirk (IEEE International Symposium on Information Theory - Proceedings, 2020)
We consider a cell-free MIMO system in uplink, comprising a massive number of distributed transmit and receive antennas. In our distributed antenna system (DAS), transmit and receive antennas are distributed according to homogeneous point processes (PP) and the received signals are processed jointly at a central processing unit (CPU). In centralized massive MIMO systems, the phenomenon of favorable propagation has been observed: when the number of receive antennas tends to infinity while the number of transmit antennas remains finite, the users' channels become almost orthogonal and low complexity detection via matched filtering is almost optimal. We analyze the properties of DASs in asymptotic conditions when the network dimensions go to infinity with given intensities of the transmit and receive antenna PPs. We study the analytical conditions of favorable propagation in DASs with two kinds of channels, namely, channels with path loss and transmit and receive antennas in line of sight (LoS) or in multipath Rayleigh fading. We show that the analytical conditions of favorable propagation are satisfied for channels impaired by path loss and Rayleigh fading while they do not hold in the case of LoS channels, motivating the use and analysis of multi-stage receivers. Simulation results of the favorable propagation conditions and the performance of multi-stage detectors for finite systems validate the asymptotic analytical results.
CRIS-Team Scopus Importer:2020-09-18